THE EFFECT OF TRANSPARENCY, ACCOUNTABILITY AND LEADERSHIP ON THE EFFECTIVENESS OF VILLAGE FUND MANAGEMENT - Christina Sososutiksno (GEMILANG: Jurnal Manajemen dan Akuntansi, 2023)
This study aims to empirically examine the effect of transparency, accountability, and leadership on the effectiveness of managing village funds in Haria village and Porto village, kec. Saparua, Kab. Central Moluccas. This research is a quantitative research using primary data, this data was obtained from respondents through a questionnaire which was distributed to 50 village government staff for data collection. The population in this study were government staff of Haria village and Porto village, Kec. Saparua Kab. Central Moluccas. Data analysis used normality test, multicollinearity test, heteroscedasticity test, and multiple linear regression test. The results of the study show that transparency affects the effectiveness of village fund management,